The adoption of biosecurity measures and its influencing factors in Bangladeshi layer farms - Mohammad Jahangir Alam; Ismat Ara Begum; Md. Abdullah Al Mamun; Md. Asif Iqbal; Andrew M. McKenzie (Discover Sustainability)
Abstract Developing nations like Bangladesh are particularly vulnerable to poultry diseases, notably Highly Pathogenic Avian Influenza. Adopting biosecurity approaches that assist farms in disease control and prevention can decrease the industry-wide dissemination of infectious diseases. In light of these factors, this study was carried out to investigate the implementation of biosecurity practices on layer farms in Bangladesh. Using a stratified random sample method, a total of 315 layer farms from fourteen upazilas (sub-districts) in seven districts were surveyed using a semi-structured interview schedule. The study explored layer farmers' experiences with biosecurity procedures adopted on farms that included equipment, employees, and visitors. The study found that the overall biosecurity score was 72.5 out of 100. It was concluded that internal biosecurity was better than external biosecurity. The study also revealed that layer farms have a larger proportion of partial adopters based on the adoption index. The application of the Tobit model identifies that education, farming experience, attitude towards risk, price of layer sheds, return from layer production, and access to biosecurity knowledge had a substantial influence on adopting biosecurity measures. The findings might be helpful for farmers and policymakers to ensure the required modifications to improve compliance with biosecurity protocols and could assist relevant authorities in implementing particular biosecurity initiatives.